Reklamlarda toplumsal cinsiyetin rolü - Doğan, Ece Işın (My University, 2011)
Reklamın başlıca amacı ürünü tanıtmak suretiyle satılmasını sağlamaktır. Reklamın, satın alma eylemi üzerinde doğrudan etkileri olmaktadır. Reklamın doğrudan etkileri kadar dolaylı etkileri de önemlidir. Mesela reklam, toplumsal cinsiyet kimliğinin oluşması ve gelişmesi üzerinde de etkili olmaktadır. Reklamlarda yer alan eril ve dişil modeller, bireylerin toplumsal cinsiyet kimliği gelişimlerini etkilemektedir. Reklamın, toplumsal cinsiyetle ilişkisi kesintisizdir. İçinde insan unsuru bulunan her reklam toplumsal cinsiyet konularıyla ilişkilenecektir. Reklamlarda, eril modeller, dişil modeller, ayrı ayrı ya da birlikte görünebilmektedirler. Başlıca dişil modelleri; anne, ev kadını ve iyi eş, çağdaş kadın ve güzel ve seksi kadın modelleri oluşturmaktadır. Başlıca eril modelleri de ev reisi, güçlü erkek, çağdaş erkek modelleri oluşturmaktadır. Reklamda erotizm ürüne dikkat çekmek için kullanılmaktadır. Erotizm ürüne direkt dikkatin çekilmesini sağlamaktadır. Reklamlarda güzel ve seksi kadınlar sıkça gösterilmektedir. Bu, esasında kadının cinsel bir obje olarak sunumu olmaktadır. Böyle olunca, eleştiri sesleri yükselmektedir. Reklamda aşırı cinsellik tepki alabilmektedir. Anahtar sözcükler: Reklam, Toplumsal cinsiyet, Toplumsal cinsiyet kimliği, Eril model, Dişil model, Erotizm, Cinsel obje.

The primary aim of advertising is to sell a product by introducing it to the consumers. There are direct effects of advertising on the purchasing movement. Besides of the direct effects of advertising, it has indirect effects; these effects are also important. For instance, advertising is also effective on the formation and development of gender identity. Several masculine and feminine models that taken part in advertisings affect the development of individuals’ gender identity. There is an uninterrupted relationship between advertising and gender. Any advertising in which found human factor will enter into relations with the gender subjects. In the advertisings, masculine models and feminine models can be seen separately or together. Main feminine models consist of the mother, housewife and good wife, modern woman, and beautiful and sexy women models. On the other hand, main masculine models consist of the head of household, strong man, and modern man models. Eroticism in advertising is used to get attention for the product. Eroticism provides directly attention to the product. Often beautiful and sexy women are showed in the advertisings. This is, essentially a presentation of woman as a sexual object. Under the circumstances directed criticisms to these advertisings increase. Excessive sex in advertising can get reactions. Advertising, Gender, Gender identity, Masculine model, Feminine model, Eroticism, Sexual object.
Keywords: Advertising; Cinsiyet rolü, Reklamcılıkta; Publicity; Reklamcılık; Sex role in advertising; Tanıtım